Temporally and Genetically Discrete Periods of Wheat Sensitivity to High Temperature - Barber, Henry M.; Lukac, Martin; Simmonds, James; Semenov, Mikhail A.; Gooding, Mike J. (Frontiers in Plant Science, 2017)
Successive single day transfers of pot-grown wheat to high temperature (35/30oC day/night) replicated controlled environments, from the second node detectable to the milky-ripe growth stages, provides the strongest available evidence that the fertility of wheat can be highly vulnerable to heat stress during two discrete peak periods of susceptibility: early booting (decimal growth stage (GS) 41-45) and early anthesis (GS 61-65). A double Gaussian fitted simultaneously to grain number and weight data from two contrasting elite lines (Renesansa, listed in Serbia, Ppd-D1a, Rht8; Savannah, listed in UK, Ppd-D1b, Rht-D1b) identified peak periods of main stem susceptibility centred on 3 (s.e.= 0.82) and 18 (s.e. = 0.55) days (mean daily temperature = 14.3oC) pre-GS 65 for both cultivars. Severity of effect depended on genotype, growth stage and their interaction: grain set relative to that achieved at 20/15oC dropped below 80% for Savannah at booting and Renesansa at anthesis. Savannah was relatively tolerant to heat stress at anthesis. A further experiment including 62 lines of the mapping, doubled-haploid progeny of Renesansa x Savannah found tolerance at anthesis to be associated with Ppd-D1b, Rht-D1b, and a QTL from Renesansa on chromosome 2A. None of the relevant markers were associated with tolerance during booting. Rht8 was never associated with heat stress tolerance, a lack of effect confirmed in a further experiment where Rht8 was included in a comparison of near isogenic lines in a cv. Paragon background. Some compensatory increases in mean grain weight were observed, but only when stress was applied during booting and only where Ppd-D1a was absent.